Culture and transcendence - Tarasti, Eero (Interdisciplinary Studies in Musicology, 2014)
Culture can be approached from an existential semiotic point of view in many ways. The following results can be then obtained: The new notion which the Existential semiotic theory of culture (ESC) tries to launch is transcendence. The ESC theory is an attempt to see and analyse issues from the inside, using a model called Zemic which refers to four modes of Being. It deals with agency like any cultural theory, but now behind the theory is the idea of a subject as a transcendental ego, who is capable of pursuing acts, making choices and enjoying freedom. The theory of ESC can be tested by empirical cases of cultural life and history such as studies in cultural heritage. The theory is non deterministic. There is “linguistic turn” in the sense that a new metalanguage is elaborated to deal with transcultural, supra-rational and metacultural issues. Formal language is used to some extent, stemming from the semiotic square, deontic logic and the grammar of modalities. The proper philosophical style is that of the continental and speculative theory, yet the ESC theory is not any regress in the history of philosophy. ESC theory is non-reductionist, i.e. it emphasizes the phenomena as such.